2020
DOI: 10.3389/fphar.2020.554777
|View full text |Cite
|
Sign up to set email alerts
|

Quality Markers for Astragali Radix and Its Products Based on Process Analysis

Abstract: Due to the complex nature of traditional medicines, quality control methods need to cover two aspects: compliance of raw materials with quality standards and process control. Astragali radix (AR), the roots of Astragalus mongholicus Bunge, was selected in this study as an example of a widely used traditional medicine in various formulations. Astragaloside IV (AG IV) and calycosin 7-O-β-D-glucoside (CG) are used as the markers for the quality control of AR and its products in the Chinese Pharmacopoeia. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As the drying temperature was increased, the total flavonoid and astragaloside IV content gradually increased, but there was no significant difference among three temperatures. The content of astragaloside IV ranged from 1.32 to 1.67 mg/g, with the highest content at 90°C, and the lowest at 70°C, this may be due to the conversion of other saponins to astragaloside IV [ 26 ]. At present, CG and astragaloside IV are used as index for the evaluation of AR quality in the Chinese Pharmacopoeia (2020 edition).…”
Section: Resultsmentioning
confidence: 99%
“…As the drying temperature was increased, the total flavonoid and astragaloside IV content gradually increased, but there was no significant difference among three temperatures. The content of astragaloside IV ranged from 1.32 to 1.67 mg/g, with the highest content at 90°C, and the lowest at 70°C, this may be due to the conversion of other saponins to astragaloside IV [ 26 ]. At present, CG and astragaloside IV are used as index for the evaluation of AR quality in the Chinese Pharmacopoeia (2020 edition).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for the difference in active constitutes content in AR between non-processed and processed subgroups is that flavonoids were unstable at higher temperatures and could transform into the aglycones form during the processing procedures [26]. Dai et al [9] have investigated the thermal stability of isoflavonoids in the water decoction and thus found that the content of calycosin 7-O-β-D-(6"-malony)-glucoside and 6"-O-malonylononin may degrade into Cal-7-O-GLU and For-7-O-GLU during the heating condition, further studies are needed to illustrate the relationship between the changes of active components content and the underlying transformation mechanisms in different processing methods.…”
Section: Effects Of Different Processing Methods On the Content Of As...mentioning
confidence: 99%
“…Heating is the major difference between the two extraction methods. Dai et al [9] demonstrated that astragaloside I, isoastragaloside I, and isoastragaloside II were unstable under heating conditions and these astragalosides may be transformed into astragaloside IV during heating. Therefore, heating, a principal factor increasing the deacetylation reaction, could cause the transformation of astragalosides [9].…”
Section: Effect Of Diameter Size On the Content Of Astragaloside IV A...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that there are over 161 saponins isolated from AR, which can be divided into cycloartane and oleanane types ( Liu Y et al, 2017 ). Among them, studies have shown that AS-IV, a quality control marker of AR ( Dai et al, 2020 ), displays a significant therapeutic effect on AD. In this section, we focused on a number of saponins which exhibit anti-AD effects through multiple pathological mechanisms, consisting of preventing the production and aggregation of Aβ, hyperphosphorylation of tau protein, anti-apoptosis, anti-inflammation, promoting the proliferation and differentiation of neural stem cells (NSCs), and so on ( Table 1 ).…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...mentioning
confidence: 99%